Analisis Keterampilan Proses Sains dalam Praktikum Kimia Fisika - Eralita, Norma (Orbital: Jurnal Pendidikan Kimia, 2023)
Physical chemistry practicum is a crucial element in higher education curriculum to develop students' science process skills. The study aims to analyze the skills of science processes in physics chemistry practices in the university environment. Emphasis is given on the ability to make careful observations, plan appropriate experiments, make accurate measurements, analyze data critically, and connect theory with practice in the laboratory. The research method used in this study is qualitative research involving data collection from physical chemistry practicum conducted by students in university laboratories. The research targets were chemical engineering students who received physical chemistry practicum courses at the faculty of industrial technology, Nahdlatul Ulama Al Ghazali University, Cilacap. Research data were collected through practicum observations, interviews, and analysis of student practicum report results. The data were analyzed to evaluate the science process skills developed during practicum, as well as its impact on the understanding of physical chemistry concepts. The results of the analysis show that physics chemistry practicums provide students with practical experience in conducting practicum activities. Students demonstrated the ability of their scientific processes to perform careful observations such as accurate and accurate measurements. Critically analyze data from the results of experiments or experiments such as making the correct table or graph. These skills are intellectual process skills that are very important in studying chemistry.